An intersection-union test for the sharpe ratio - Gabriel Frahm (Risks, 2018)
An intersection-union test for supporting the hypothesis that a given investment strategy is optimal among a set of alternatives is presented. It compares the Sharpe ratio of the benchmark with that of each other strategy. The intersection-union test takes serial dependence into account and does not presume that asset returns are multivariate normally distributed. An empirical study based on the G-7 countries demonstrates that it is hard to find significant results due to the lack of data, which confirms a general observation in empirical finance.
Keywords: C12; G11; 330; ergodicity; Gordin's condition; heteroscedasticity; intersection-union test; Jobson-Korkie test; performance measurement; Sharpe ratio